(untitled) (Journal of Parents and Teachers, 2024)
The article highlights the importance of personalized education and vocational training for young people, emphasizing the need for programs that integrate work and social skills. The relevance of educational guidance and complementary activities that foster social integration and personal development is mentioned. In addition, collaboration with social institutions is suggested to enrich the educational experience and facilitate the transition to active life.